Modern Language Instruction at Community College: A Survey‐Based Study of Modern Language Instructors. (18th August 2017) - Nagano, Tomonori; Funk, Alexander; Ketcham, Eric
Abstract: This article presents and analyzes instructor data from the Students and Instructors of Languages at Community Colleges (SILCC) Survey. The SILCC Survey was designed to collect data from language professionals teaching at community colleges (CCs) on the specific challenges, opportunities, and potential areas of growth in their field. Results from 140 instructor responses in 101 CCs in 33 U.S. states are used to document the current state of teaching and learning of modern languages at CCs through a systematic survey procedure. The data on modern language instruction at CCs, a segment of the U.S. educational system underrepresented in scholarly discussions in the field of modern language, shows both strengths and areas in need of improvement.